المقارنة بين تكراريتي S.Thianwan, Agarwal لمؤثرات Zamfirescu - متيلج, عدنان (Latakia University Journal -Basic Sciences Series, 2018)
نبرهن في هذه المقالة التكافؤ بين تكراريتي S.Thianwan, Agarwal من أجل تطبيقات Zamfirescu المعرفة على مجموعات جزئية محدبة ومغلقة وغير خالية من فضاءات باناخ, ثم نثبت أن تكرارية Agarwal تتقارب إلى نقطة ثابتة لمؤثر Zamfirescu بسرعة أكبر من تقارب تكرارية S.Thianwan . وأخيراً تمت دراسة مثال تطبيقي بمساعدة برنامج باسكال . In this paper we prove that the Agarwal, S. Thianwan iterative schemes are equivalent for – Zamfirescu operators defined on an arbitrary closed convex subset of a Banach spaces. In addition , we proved that the Agarwal iteration converges is faster than the S. Thianwan iterations to the fixed point of Zamfirescu operator .Finally we solved a practical example using the Pascal program.